Integration of the Baltic states into the EU and institutions of fiscal convergence: A critical evaluation of key issues and empirical evidence - Ali M. Kutan; Niina Pautola-Mol (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2001)
This paper reviews the issues concerning the integration of the Baltic States into the European Union (EU). The focus is on fiscal policy and institutions of policy convergence. More specifically, we evaluate the functioning, suitability, and effectiveness of the Maastricht convergence criteria on fiscal policy and the Stability and Growth Pact for Estonia, Latvia, and Lithuania. Using the European Commission's approach, we estimate output gap measures to provide empirical evidence on fiscal discipline and cyclical sensitivity of each state's budget to changes in output. Empirical evidence indicates that Estonia and Latvia have been more successful in maintaining fiscal discipline than Lithuania during 1996-2000. Evidence on the cyclical sensitivity of the Baltic States suggests that the Stability and Growth Pact signed in July 1997 would offer enough room for automatic fiscal stabilizers in Estonia and Latvia, but not in Lithuania. Implications of our results for future perspectives are also discussed.
Keywords: 330